PEMAHAMAN WACANA PADA PROSES KOMUNIKASI LINTAS BUDAYA - Efrizal (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
Cross-cultural misunderstanding is the one of the process of cross-cultural miscommunication each day in social life. Interaction in social stratum is packed by the system which call “cultural,” and the interaction of it is about the intervalues and internorms in that cultural. Therefore, preventing to cross-cultural misunderstanding is needed the way to be able indicator to create the harmonious interaction and understanding of cross-cultural communication. This article purpose to uncover using “contextualization cues” which explained by Gumperz (1982) as effort preventing misunderstanding in the process of cross-cultural communication. Contextualization cues is used to interaction in interrelatedness of interlanguage and intercultural. This article will give too the misunderstanding illustration differences about interpreting and the cultural values in the process cross-cultural communication, and then to express what the “contextualization cue” be able to have a role as instrument in study of cross- cultural misunderstanding.